Artificial seagrass: a habitat for marine fishes - Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman; Mohammad Noor, Normawaty; Tan, Chit Dah; John, Akbar (Academic Journals, 2011)
Artificial seagrass plays an important role for the distribution of benthic organisms and fishes. Based on this perspective a study was conducted in the Sepanggar Bay located in the Northern part of Kota Kinabalu, Malaysia from November 2006 to February 2007 to determine the potentiality of artificial seagrass as an alternative habitat for marine fishes. The artificial seagrass area is located approximately 100 m from the coastline at the depth between 6 and 10 m and made up of Dorken Advance Engineer Rubber which was tightened on a square 1 x 3 m metal mat. The sampling process was done by capturing photos and video recording. The picture of the fishes was taken as many as possible to increase the accuracy and precision of fish identification. A total of 497 fish species belong to 17 families were observed in 5 sampling periods throughout the study. Out of 17 families, Pomacentridae was dominant with 25.55% (127 individuals) followed by caesionidae with 22.13% (110 individuals). It was observed that Caesio sp. from a family Caesionidae was dominant genus in the artificial seagrass area, followed by Chromis sp. and Pomacentrus sp. from a family Pomacentridae. Overall Shannon diversity (H’) value of 2.5315 indicates artificial sea grass could play a vital role as a nutrient rich habitat for marine fishes